Ancient Tradition as Ongoing Creation: The Kathavacaks of Uttar Pradesh - Walker, Margaret (MUSICultures, 2006)
In the North Indian state of Uttar Pradesh live rural folk performers who identify themselves as Kathavacaks. These artists present a form of story-telling they call kathavacan, which combines song, speech, and gestures punctuated by rhythmic interludes. Part of a larger clan of hereditary musicians and dancers, they connect themselves most closely to a family of dancers who perform the classical stage dance called kathak. These urban relatives and some scholars now identify kathavacan as the ancient and devotional root of the classical dance. After providing a description of kathavacan performance, this article examines the various claims of ancient origins and temple performance in the context of insider agency and activism. In this case, there is considerable evidence of an ongoing endeavour by these hereditary musicians to disseminate a chosen identity as ancient tradition largely through documentation by cultural outsiders.